Keistimewaan Kebudayaan Arab dan Islam di Kawasan Timur Tengah (Pakaian, Kerudung, Gelar-Gelar, Tradisi Perayaan Umum dan Sastra) - Muslimin, Muhammad Irwin; Nurwahidin, Nurwahidin (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
The Middle East has a large population and also has several countries in this region. Its diversity makes Middle Eastern life very diverse in its cultural features. The Middle East region has many cultural values. Cultural values including of customs, habits, literature, and others. This qualitative research used a library research approach and a descriptive-analytical method which aims to provide an overview of the topics related to the peculiarities of Middle Eastern and Islamic culture, especially in terms of apparel, headscarves, appellation, the ceremonies of general practice, and literature based on data collected. Draw by the researcher. The result of the study indicates that Middle Eastern apparel follows what has existed in earlier times. In the pre-Islamic era, Middle Eastern clothing was generally long, loose clothes with several shapes depending on the region. The use of the veil also existed in pre-Islamic times and was used by Malian women, Hindus, Jews, and Christians. At that cadence, the veil was used as a marker for women when leaving the house. Islam has come to bring a new idea to dressing because in Islamic teachings it is obligatory to cover the genitals. The Middle East also has privileges such as titles, public historical events are different from other regions (Eid al-Fitr, Eid al-Adha, weddings, and funerals), and beautiful literary writings.